The Influence Of Customer Understanding On Interest In Waqf With Moderating Religiosity - Harni; Mukhtar Lutfi; Nasrullah Bin Sapa (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
Social inequality and low community participation in cash waqf through Cash Waqf Linked Sukuk CWLS indicate that the great potential of waqf has not been optimized. Lack of financial literacy, access to services, and traditional perceptions of waqf are the main obstacles. This study is important to identify factors that influence community waqf intentions, especially in CWLS products. The purpose of this study is analyze and explain the influence of financial literacy, financial inclusion, socialization, and marketing programs on waqf intentions on CWLS with religiosity as a moderator. The population of this study were all customers of Bank Syariah Indonesia, with a sampling technique using purposive sampling. The number of samples that met the criteria was 150 customers. Hypothesis testing was carried out using SEM-PLS. The results of the study showed that financial literacy, socialization, and marketing programs had a significant positive effect on waqf intentions, while financial inclusion had no significant effect. Religiosity as a moderator strengthens the influence of socialization and marketing programs on waqf intentions, but weakens the influence of financial literacy and inclusion. These findings indicate the importance of CWLS education and marketing strategies integrated with religious and social approaches to increase community participation in waqf.